Efektivitas Model Pembelajaran Interaktif Explicit Instruction Terhadap Hasil Belajar Menulis Karangan Eksposisi Murid Kelas V SD Negeri 7 Tekolabbua Kabupaten Pangkajene dan Kepulauan - Nurul Hidayah Nindya Pratiwi (CV Edujavare Publishing, 2024)
The purpose of this study was to describe the effectiveness of the interactive explicit instruction learning model on the learning outcomes of exposition writing skills of grade V students at SD Negeri 7 Tekolabbua, Pangkajene and Kepulauan Regency. This type of research is experimental research. The population in this study were grade V students of SD Negeri 7 Tekolabbua, Pangkajene and Kepulauan Regency totaling 18 people in the 2024/2025 academic year. The sampling technique was a saturated sample. The sample in this study was the entire population sampled as many as 18 people. Data collection techniques consisted of an initial test (pretest), treatment (treatment) and a final test (posttest). Data analysis techniques included descriptive statistical data analysis and inferential statistical data analysis. The results showed that the implementation of exposition writing learning with the interactive explicit instruction learning model for grade V students of SD Negeri 7 Tekolabbua, Pangkajene and Kepulauan Regency, obtained tCount = 8.19 and tTable = 2.11, then obtained tCount> tTable or 8.19> 2.11. It can be concluded that the application of the interactive explicit instruction learning model is effective in teaching expository writing to fifth grade students of Elementary School 7 Tekolabbua, Pangkajene and Kepulauan Regency.